Pengaruh Efektifitas Pembelajaran, Pelatihan Dan Sertifikasi Kompetensi Pegawai Terhadap Kinerja Pegawai PT PLN (Persero) UPT Malang - Wahid Syaifudin; Budi Wahono; Restu Millaningtyas (UNIVERSITAS ISLAM MALANG, 2022)
AbstractAll activities, both managerial and operational within the company, are the responsibility of human resources within the company. This study aims to determine the effect of the effectiveness of learning, training and certification on employee performance at PT PLN (Persero) UPT Malang simultaneously and partially. This type of research is quantitative associative research. The research was conducted at PT PLN (Persero) Malang Transmission Implementing Unit. The time of this research will be carried out from January to November 2021. The population used is employees of PT PLN (Persero) UPT Malang, totaling 145 people. While the size of the research sample amounted to 51 respondents. Based on the results of the study, it is known that simultaneously the variables of the effectiveness of learning, training and certification have an effect on employee performance at PT PLN (Persero) UPT Malang. Partially or individually the variables of the effectiveness of learning, training and certification affect the performance of employees at PT PLN (Persero) UPT Malang. Keywords: Learning Effectiveness, Training, Certification, Employee Performance